Structural Ensembles of Membrane-bound α-Synuclein Reveal the Molecular Determinants of Synaptic Vesicle Affinity - Fusco, Giuliana (Sci Rep, 2016)
A detailed characterisation of the molecular determinants of membrane binding by α-synuclein (αS), a 140-residue protein whose aggregation is associated with Parkinson’s disease, is of fundamental significance to clarify the manner in which the balance between functional and dysfunctional processes are regulated for this protein. Despite its biological relevance, the structural nature of the membrane-bound state αS remains elusive, in part because of the intrinsically dynamic nature of the protein and also because of the difficulties in studying this state in a physiologically relevant environment. In the present study we have used solid-state NMR and restrained MD simulations to refine structure and topology of the N-terminal region of αS bound to the surface of synaptic-like membranes. This region has fundamental importance in the binding mechanism of αS as it acts as to anchor the protein to lipid bilayers. The results enabled the identification of the key elements for the biological properties of αS in its membrane-bound state.